1999
DOI: 10.3354/meps184043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ferredoxin and flavodoxin as markers of iron limitation in marine phytoplankton

Abstract: Under conditions of iron stress, many organisms replace the comlnon iron-sulfur redox protein ferredoxin with flavodoxin, a functionally equivalent, non-iron-containing protein These 2 proteins have been proposed to be ind~cators of iron nutritional status in marine phytoplankton, but llttle is known of their expression and regulation. This study charactenzed their expression by. (1) testing 17 marine phytoplankton lsolates from 4 different algal classes for their ability to induce flavodoxin under iron limtat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 29 publications
3
88
0
Order By: Relevance
“…It is not clear, then, why a genetic trait that confers such obvious advantages was not selected during the evolution of terrestrial plants. Fld has been found in the plastids of eukaryotic algae belonging to all major families (19), suggesting that the gene was lost in the green algal precursor or in the primitive plants. Fld loss might be related to ecological adaptations, but a systematic appraisal of this possibility will require an extensive survey of Fld-proficient and -deficient clones between algal groups and habitats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is not clear, then, why a genetic trait that confers such obvious advantages was not selected during the evolution of terrestrial plants. Fld has been found in the plastids of eukaryotic algae belonging to all major families (19), suggesting that the gene was lost in the green algal precursor or in the primitive plants. Fld loss might be related to ecological adaptations, but a systematic appraisal of this possibility will require an extensive survey of Fld-proficient and -deficient clones between algal groups and habitats.…”
Section: Discussionmentioning
confidence: 99%
“…An example of such an adaptation is provided by some cyanobacteria and marine algae that, when exposed to Fe-deficient conditions, induce the expression of flavodoxins (Fld), small redox proteins harboring one molecule of flavin mononucleotide as prosthetic group (6,(19)(20)(21). These soluble electron carriers are able to replace Fe-containing ferredoxin (Fd) in many different processes, including photosynthesis (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present there are only a few methods and indicators that have been identified for nutrient limitation of phytoplankton species in the natural environment. For example, diagnostics such as glutamine:glutamate (GLN/GLU; 14 Flynn et al 1989; and ferridoxin:flavodoxin (Fd index; Erdner et al 1999), have been related to specific limitations or stresses (nitrogen and iron) in laboratory cultures and in some cases have been used to monitor changes in nutritional stress in the natural environment (LaRoche et al 1996;Erdner and Anderson 1999). However, in most cases standard bulk analyses of the phytoplankton community, such as chlorophyll, primary production, or nutrient uptake, are not useful since they provide data for the entire planktonic community rather than an individual species, such as A. fundyense.…”
Section: Physiology Toxin Content and Composition Once Methods Of Dmentioning
confidence: 99%
“…When iron limited, cells may temporarily replace iron-requiring proteins with less efficient iron-free functional equivalents to minimize their iron demands, including the alternation between the iron-containing photosynthetic electron transfer protein ferredoxin and the iron-free version flavodoxin (14,15). Most cultured isolates of diatoms preferentially use ferredoxin when grown under iron-replete conditions (16)(17)(18) although inconsistencies between laboratory and field studies have been reported (5,19). In some instances, reliance on iron-free versions of proteins may be permanent.…”
mentioning
confidence: 99%